Management, information systems and technologies in health care : analysis of current status in hospitals of Eastern Slovakia - Gavurová, Beáta, 1972-; Šoltés, Marek, 1974- (Petru Maior University of Târgu Mureş, 2012)
Scientific monograph presents analysis of management of health care organizations and utilization of information systems and technologies in different areas of their activities. Universal methodology of analysis and definition of strategic objectives and values is described.